Subprime Consumer Credit Demand: Evidence from a Lender's Pricing Experiment - Alan, Sule; Loranth, Gyongyi (Review of Financial Studies, 2013)
[Using a unique panel data set from a U.K. credit card company, we analyze the interest rate sensitivity of subprime credit card borrowers. In addition to all individual transactions and loan terms, we have access to details of a randomized interest rate experiment conducted by the lender on existing (inframarginal) loans. For the whole sample, we estimate a statistically significant £3.4 reduction in monthly credit demand in response to a five percentage point increase in interest rates. This aggregate response is small, but it masks very interesting heterogeneity in the sample. We find that only low-risk borrowers who fully utilize their credit cards lower their credit demand significantly when faced with an increase in interest rates. We also document that a five percentage point increase in interest rates generates significant additional revenue for the lender without inducing delinquency over a short horizon.]